2014
DOI: 10.1175/jcli-d-14-00339.1
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Tropical-Like Cyclones in Present and Future Climate

Abstract: The Mediterranean has been identified as one of the most responsive regions to climate change. It has been conjectured that one of the effects of a warmer climate could be to make the Mediterranean Sea prone to the formation of hurricanes. Already in the present climate regime, however, a few of the numerous low pressure systems that form in the area develop a dynamical evolution similar to the one of tropical cyclones. Even if their spatial extent is generally smaller and the life cycle shorter compared to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 28 publications
7
95
0
Order By: Relevance
“…The largest reductions occur in Autumn (September-November) and Spring (March-May), while small changes are found in Winter (December-February). Although the significance of the changes in individual seasons is low (the p values are 0.12 in Autumn and 0.18 in Spring), it suggests that the active medicane season will tend to be become more limited in winter, which is consistent with findings of Cavicchia et al (2014b). Chang (2014) suggests that MSLP might be a very poor way of looking at the changes in cyclone intensity as mean changes in MSLP project onto changes in the extremes, so the wind speed changes are the most important variable to analyse in the vicinity of the track.…”
Section: Future Climatesupporting
confidence: 79%
See 1 more Smart Citation
“…The largest reductions occur in Autumn (September-November) and Spring (March-May), while small changes are found in Winter (December-February). Although the significance of the changes in individual seasons is low (the p values are 0.12 in Autumn and 0.18 in Spring), it suggests that the active medicane season will tend to be become more limited in winter, which is consistent with findings of Cavicchia et al (2014b). Chang (2014) suggests that MSLP might be a very poor way of looking at the changes in cyclone intensity as mean changes in MSLP project onto changes in the extremes, so the wind speed changes are the most important variable to analyse in the vicinity of the track.…”
Section: Future Climatesupporting
confidence: 79%
“…This reduction in the total number of medicanes (−30 %) is consistent with previous studies. For example, Cavicchia et al (2014b) found a reduction of about 20-60 % depending on the emission scenario, by applying dynamical downscaling to a global climate model while Romero and Emanuel (2013) estimated a reduction of 10-40% depending on the GCM used. Projected changes in medicane frequency for individual seasons are presented in Fig.…”
Section: Future Climatementioning
confidence: 99%
“…In this context, the future variations of medicane characteristics due to climate change are a matter of concern. RCMs have been used to downscale global climate model (GCM) scenarios (Gaertner et al 2007;Cavicchia et al 2014;Walsh et al 2014). Romero and Emanuel (2013) applied a statistical-deterministic method for increasing the medicane sample size.…”
Section: Introductionmentioning
confidence: 99%
“…For future climate scenarios, a decrease in storm occurrence was found, due to increased atmospheric stability in analogy to the Polar Lows case. On the other hand a slight intensification of the occurring future storms was found (Cavicchia et al 2014b). As an example, Figure 4 shows the spatial densities of medicanes (given as number of tracks passing through a grid box) and the interannual variability.…”
Section: Simulating Small Synoptic Features Conditioned By the Large-mentioning
confidence: 99%